DETERMINAN NILAI PERUSAHAAN SUB SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Muhammad Fauzi (2022)
This research is a quantitative research which has the aim of knowing the effect of Capital Structure proxied by Debt Equity Ratio (DER), Liquidity proxied by Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio which is proxied by Capital Adequacy Ratio (CAR) on Company Value as proxied Price to Book Value (PBV). This study examines the population of the financial sector listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The technique used in this research is using purposive sampling technique to obtain 180 research sample data. The analysis carried out in this study using Microsoft Excel 2013 and hypothesis testing using Panel Data Regression Analysis with the Eviews version 12 application and a significance level of 5%. The results of the study partially show that, (1) Capital Structure has an effect on Firm Value, (2) Liquidity has an effect on Firm Value, and (3) Capital Adequacy has an effect on Firm Value